Effects of copper salts on performance, antibiotic resistance genes, and microbial community during thermophilic anaerobic digestion of swine manure. (March 2020) - Wu, Xiayuan; Tian, Zhenzhen; Lv, Zuopeng; Chen, Zixuan; Liu, Yongdi; Yong, Xiaoyu; Zhou, Jun; Xie, Xinxin; Jia, Honghua; Wei, Ping
Graphical abstract: Highlights: Mixed inorganic/organic Cu had positive effects on AD performance and ARGs removal. These positive effects might be due to the low bioavailability of mixed Cu salts. The highest Clostridia _MBA03 and Methanobacterium abundances were in mixed Cu group. Microbial community induced by environmental factors mainly determined ARGs profiles. Mixed Cu could be an alternative to replace inorganic Cu in animal feed additives. Abstract: This study investigated methane production and ARGs reduction during thermophilic AD of swine manure with the addition of different Cu salts (cupric sulfate, cupric glycinate, and the 1:1 mixture of these two salts). Results showed methane production was increased by 28.78% through adding mixed Cu salts. The mixed Cu group effectively reduced total ARGs abundance by 26.94%, suggesting mixed Cu salts did not promote the potential ARGs risk. The positive effects of mixed Cu salts on AD performance and ARGs removal might be ascribed to the low bioavailability. Microbial community analysis indicated the highest abundances of Clostridia _MBA03 and Methanobacterium in the mixed Cu group might cause the increased methane production. Spearman's rank correlation analysis elucidated the succession in microbial community induced by environmental factors was the main driver for shaping ARGs profiles. Thus, mixed Cu salts could be an alternative to replace the inorganic Cu salt in animal feed additives.